The miracles among us : how God's grace plays a role in healing - Siegel, Marc (Marc K.) (Fox News Books, 2025)
"Almost everything a doctor sees can be explained scientifically. Almost. Drawing from his extensive experience as a physician, Dr. Marc Siegel explores the profound and often mysterious intersection between faith and medicine. He shares riveting stories of patients who have experienced remarkable recoveries, challenging the boundaries of medical science. These narratives highlight not only the resilience of the human body, but also the inexplicable moments when intuition and foresight play a crucial role in healing. Doctors see more than just patients who are cured against all odds. Doctors see more than just patients who are cured against all odds. From a rabbi who somehow knew a carpenter's infant son had a heart problem, to an NFL player's amazing survival from a rare kind of cardiac arrest, these stories bolster the belief there is a higher power at work. The Miracles Among Us reminds us that God's love has the capacity to surprise us even in our darkest moments. Whether you are a healthcare professional, a patient, or simply someone intrigued by the mysteries of medicine, this book provides an enlightening exploration of how miracles manifest in everyday life."--